Aortic root dimension and arterial stiffness in arterial hypertension: the Campania Salute Network. Issue 6 (June 2016) - Lønnebakken, Mai Tone; Izzo, Raffaele; Mancusi, Costantino; Losi, Maria Angela; Stabile, Eugenio; Rozza, Francesco; Gerdts, Eva; Trimarco, Bruno; de Luca, Nicola; de Simone, Giovanni
Abstract : Objectives: The relation between aortic root dimension (ARD) and measures of arterial stiffness is uncertain. Accordingly, we studied the relation between ARD and an estimate of arterial stiffness in 12 392 hypertensive patients (age 53 ± 12 years, 43% women) free of prevalent cardiovascular disease and with ejection fraction at least 50%, from the Campania Salute Network Registry. Methods: Echocardiographic ARD was measured and compared with the value predicted by age, sex and height by using a z -score. Arterial stiffness was assessed by the pulse pressure/stroke index. The highest population tertile of pulse pressure/stroke index was considered 'high arterial stiffness'. Results: High arterial stiffness was more common in women than in men ( P < 0.001) and associated with older age, diabetes, longer duration of hypertension and less frequent smoking habit (all P less than 0.01). Patients with high arterial stiffness had smaller ARD, higher carotid intima–media thickness and plasma cholesterol, and lower BMI and glomerular filtration rate (all P less than 0.01). In multivariable logistic analysis, high arterial stiffness was associated with both lower ARD z -score [OR 0.83 (95% confidence interval 0.79–0.88)] and higher carotid intima–media thickness [OR 1.36 (95% confidence interval 1.26–1.47); both P less than 0.0001], independent of significant associations with age, female sex, body size, DBP, heart rate, duration of hypertension, diabetes and smoking habit. Conclusion: Small ARD, together with atherosclerotic modifications of conduit arteries, is associated with increased 2-element Windkessel model of arterial stiffness in hypertension, independently of the significant effect of confounders.